2023
DOI: 10.1002/wsb.1449
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to ban lead ammunition: a comparison between Europe and the United States

Abstract: The human health impacts of lead have been known for millennia but the environmental impacts of lead ammunition have only received attention during the past 100 years. To a large extent the United States provided leadership in identifying and researching these effects and then spearheading campaigns to transition away from lead shotgun ammunition for waterfowl hunting. However, the appetite for further federal transition has largely stalled in the U.S. except for apparently limited action linked to individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…The best estimate of the percentage of pheasants expected to be killed using lead shot in the last season of the transition period (2024/2025), as projected from the fitted regression model, is that it will be about 84%. It has been argued that, because we do not find shot in all pheasant carcasses dissected, the SHOT-SWITCH measure of the proportion of carcasses in which any shot is found that contain lead might overestimate the proportion of pheasants killed with lead pellets (Green et al 2023b;Ellis & Miller 2023). This would be true if non-lead shot were more likely than lead to pass through the bird's body without embedding in it.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The best estimate of the percentage of pheasants expected to be killed using lead shot in the last season of the transition period (2024/2025), as projected from the fitted regression model, is that it will be about 84%. It has been argued that, because we do not find shot in all pheasant carcasses dissected, the SHOT-SWITCH measure of the proportion of carcasses in which any shot is found that contain lead might overestimate the proportion of pheasants killed with lead pellets (Green et al 2023b;Ellis & Miller 2023). This would be true if non-lead shot were more likely than lead to pass through the bird's body without embedding in it.…”
Section: Discussionmentioning
confidence: 75%
“…The 95% bootstrap confidence interval for this percentage (71% to 135%) indicates that it is unlikely that there is a difference in the proportions of birds from which shot were recovered between those killed using lead and non-lead shot large enough to bias our estimates substantially in either direction. We therefore do not consider that the measure proposed by Ellis & Miller (2023) is an accurate alternative to the one we have used. However, we note that, even if it is adopted, analysis of the results shown in Table 1 indicates no evidence for a downward trend over time in the proportion of pheasants killed using lead shotgun ammunition in response to the voluntary transition.…”
Section: Changes Across Shooting Seasonsmentioning
confidence: 97%
See 2 more Smart Citations